Comparison of the accuracy of Hybrid Capture II and polymerase chain reaction in detecting clinically important cervical dysplasia: a systematic review and meta-analysis - Luu, Hung N (Blackwell Publishing Ltd, 2013)
The effectiveness of screening programs for cervical cancer has benefited from the inclusion of Human papillomavirus (HPV) DNA assays; which assay to choose, however, is not clear based on previous reviews. Our review addressed test accuracy of Hybrid Capture II (HCII) and polymerase chain reaction (PCR) assays based on studies with stronger designs and with more clinically relevant outcomes. We searched OvidMedline, PubMed, and the Cochrane Library for English language studies comparing both tests, published 1985–2012, with cervical dysplasia defined by the Bethesda classification. Meta-analysis provided pooled sensitivity, specificity, and 95% confidence intervals (CIs); meta-regression identified sources of heterogeneity. From 29 reports, we found that the pooled sensitivity and specificity to detect high-grade squamous intraepithelial lesion (HSIL) was higher for HCII than PCR (0.89 [CI: 0.89–0.90] and 0.85 [CI: 0.84–0.86] vs. 0.73 [CI: 0.73–0.74] and 0.62 [CI: 0.62–0.64]). Both assays had higher accuracy to detect cervical dysplasia in Europe than in Asia-Pacific or North America (diagnostic odd ratio – dOR = 4.08 [CI: 1.39–11.91] and 4.56 [CI: 1.86–11.17] for HCII vs. 2.66 [CI: 1.16–6.53] and 3.78 [CI: 1.50–9.51] for PCR) and accuracy to detect HSIL than atypical squamous cells of undetermined significance (ASCUS)/ low-grade squamous intraepithelial lesion (LSIL) (HCII-dOR = 9.04 [CI: 4.12–19.86] and PCR-dOR = 5.60 [CI: 2.87–10.94]). For HCII, using histology as a gold standard results in higher accuracy than using cytology (dOR = 2.87 [CI: 1.31–6.29]). Based on higher test accuracy, our results support the use of HCII in cervical cancer screening programs. The role of HPV type distribution should be explored to determine the worldwide comparability of HPV test accuracy.